Histopathological and Molecular Characterization of Liver Fibrosis Induced by Chronic Viral Hepatitis - Sadiq Salam H. Al-Salih; Nada Khazal K. Hindi; Fadhilah N. Alobaidan (Journal of Biomedicine and Biochemistry, 2025)
Chronic hepatitis B and C infections remain major causes of liver fibrosis and cirrhosis worldwide. This study aims to correlate histopathological features with molecular markers of fibrogenesis in liver biopsy samples from infected patients. Sirius Red staining quantified fibrosis, while RT- qPCR assessed the expression of TGF-β1, COL1A1, and α-SMA. Our findings reveal that increased expression of fibrogenic genes correlates with fibrosis stage and clinical outcomes. These data provide valuable insights for the identification of molecular targets for antifibrotic therapy and highlight the importance of early intervention in chronic viral hepatitis.